Importância do colesterol para a mecânica celular e para a entrada do Trypanosoma cruzi na célula hospedeira - Barbara Hissa de Carvalho Vieira Couto (2013)
In the present work we have investigated the importance of cholesterol in controlling mechanical properties of cells and how this modulates Trypanosoma cruzi entry in host cells. For this we performed studies of cell membrane dynamics using tether extraction with optical tweezers (OT) and defocusing microscopy (DM), as well as lysosomal exocytosis and T. cruzi invasion assays in a mouse fibroblast cell line (WTCL3) and primary cultures of neonatal murine cardiomyocytes. We observed, by OT, that both bending rigidity and surface tension increased when WTCL3 was treated with MCD, a drug that sequesters cholesterol from cell membranes. Additionally, by DM, we demonstrated that membrane-cytoskeleton relaxation time increased in the beginning of MCD treatment and decreased in the end, assuming values similar to control. With this technique we have also proved that the amplitude of oscillation diminished during cholesterol depletion, showing that these cells become stiffer. Together, these changes in membrane dynamics involved not only the actin cytoskeleton rearrangement, but also its polymerization de novo and stress fiber formation through Rho activation.Additionally, for cardiomyocytes and fibroblasts, we have proved that treatment with MCD, but not with a similar cyclodextrin with less affinity for cholesterol, triggered lysosome secretion and that this phenomenon was independent of extracellular and intracellular calcium, at least for cardiomyocytes. By using NRK cells we have also shown that lysosome exocytosis, in the absence of cholesterol, continued to happen even in the absence of synaptotagmin-VII, the calcium sensor protein present in these organelles. Exocytosis triggered by cholesterol removal led to the secretion of lysosomes located near the cell cortex, different from the pool recruited by actin depolymerizing drugs, such as latrunculin-A. These data suggest the existence of at least two different pools with different exocytosis dynamics. It is well known that T. cruzi needs both a relatively malleable actin cytoskeleton and a reservoir of cortical lysosomes in order to invade cells successfully. Although there are evidences that plasma membrane cholesterol is important for T. cruzi invasion, since it diminishes severely after cyclodextrin treatment, in none of them wasestablished a mechanism by which cholesterol interferes with T. cruzi entry. In this work we showed that for cardiomyocytes, an important cell during host infection, cholesterol depletion not only diminishes T. cruzi invasion, but also its association with lysosomal markers at the initial steps of host cell entry. The membrane dynamics change (increasing cortical energy barrier) and lysosomal exocytic events (depleting the cortical lysosome reservoir), triggered by cholesletrol sequestration, are most likely the mechanisms y which cholesterol depletion interferes withparasite host cell invasion.